Bacterial community composition in the salivary glands of triatomines (Hemiptera: Reduviidae). - Michele Souza Lima; Marinella Silva Laport; Elias Seixas Lorosa; José Jurberg; Kátia Regina Netto Dos Santos; Mário Alberto Cardoso da Silva Neto; Caio Tavora Coelho da Costa Rachid; Georgia Correa Atella (Public Library of Science (PLoS), 2018)
BACKGROUND:Chagas disease is caused by the parasite Trypanosoma cruzi and is transmitted through triatomines (Hemiptera: Reduviidae). In the last year, many studies of triatomine gut microbiota have outlined its potential role in modulating vector competence. However, little is known about the microbiota present in the salivary glands of triatomines. Bacterial composition of salivary glands in selected triatomine species was investigated, as well as environmental influences on the acquisition of bacterial communities. METHODOLOGY/PRINCIPAL FINDINGS:The diversity of the bacterial communities of 30 pairs of salivary glands of triatomines was studied by sequencing of the V1- V3 variable region of the 16S rRNA using the MiSeq platform (Illumina), and bacteria isolated from skin of three vertebrate hosts were identified based on 16S rRNA gene sequence analysis (targeting the V3-V5 region). In a comparative analysis of microbiota in the salivary glands of triatomine species, operational taxonomic units belonging to Arsenophonous appeared as dominant in Triatoma spp (74% of the total 16S coverage), while these units belonging to unclassified Enterobacteriaceae were dominant in the Rhodnius spp (57% of the total 16S coverage). Some intraspecific changes in the composition of the triatomine microbiota were observed, suggesting that some bacteria may have been acquired from the environment. CONCLUSIONS AND SIGNIFICANCE:Our study revealed the presence of a low-diversity microbiota associated to the salivary glands of the evaluated triatomines. The predominant bacteria genera are associated with triatomine genera and the bacteria can be acquired in the environment in which the insects reside. Further studies are necessary to determine the influence of bacterial communities on vector competence.